2001
DOI: 10.1029/2001jb000179
|View full text |Cite
|
Sign up to set email alerts
|

Crustal and upper mantle structure beneath Antarctica and surrounding oceans

Abstract: Abstract. We present and discuss a new model of the crust and upper mantle at high southern latitudes that is produced from a large, new data set of fundamental mode surface wave dispersion measurements. The inversion for a 2 ø x 2 ø shear velocity model breaks into two principal steps: first, surface wave tomography in which dispersion maps are produced for a discrete set of periods for each wave type (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
234
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(252 citation statements)
references
References 76 publications
(33 reference statements)
17
234
0
1
Order By: Relevance
“…Seismic studies suggest a significant difference in Earth structure between East Antarctica and West Antarctica, with expectation of a thicker lithosphere in East Antarctica (Ritzwoller et al 2001). Compared to the rest of West Antarctica, the Antarctic Peninsula has a much thinner lithosphere and lower mantle viscosity associated with ancient plate subduction in this region (Simms et al 2012, Ivins et al 2011, Yegorova et al 2011.…”
Section: 35mentioning
confidence: 99%
“…Seismic studies suggest a significant difference in Earth structure between East Antarctica and West Antarctica, with expectation of a thicker lithosphere in East Antarctica (Ritzwoller et al 2001). Compared to the rest of West Antarctica, the Antarctic Peninsula has a much thinner lithosphere and lower mantle viscosity associated with ancient plate subduction in this region (Simms et al 2012, Ivins et al 2011, Yegorova et al 2011.…”
Section: 35mentioning
confidence: 99%
“…[32] The buried sources of the high-amplitude NW trending anomalies are most likely to be Precambrian basement older than Neoproterozoic age, based on the presence of Archean-Paleoproterozoic igneous and metamorphic rocks in the Nimrod Group, the thick high-velocity lithosphere imaged by seismic tomography in the region Morelli and Danesi, 2004;Ritzwoller et al, 2001], and the high amplitude of positive anomalies observed both in satellite data over the polar plateau and in the western end of our survey . In addition, the similarly oriented but finer-scale magnetic structure of the Nimrod basement complex (magnetic unit 1), whose magnetization was produced during Ross age metamorphism, probably reflects tectonic modification of preexisting Precambrian basement structure.…”
Section: Sources Of Buried Magnetic Anomaliesmentioning
confidence: 99%
“…Because of the lack of continuation to a common elevation above the bed and the different flight line spacings, the amplitudes and wavelengths of anomalies from similar sources can vary from survey to survey. Despite such limitations, all of these data, combined with bed elevation [Ferraccioli et al, 2009;Lythe et al, 2000;Studinger et al, 2004Studinger et al, , 2006 and regional seismic tomography data [Morelli and Danesi, 2004;Ritzwoller et al, 2001], help to resolve critical features of the craton and outboard sequences. In particular, the western limit of the Neoproterozoic rift, and the extent of the Ross Orogen and Jurassic Ferrar dolerites can be mapped in more detail (Figure 9) than previously possible .…”
Section: Precambrian Crustal Elements From the Ctam Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…The eastern edge of highvelocity perturbations interpreted to relate to the Precambrian shield of East Antarctica (Ritzwoller et al, 2001) is approximately coincident with the eastern edge of the satellite magnetic high (Fig. 2).…”
Section: Aeromagnetic Signatures Of the Mawson Block And Adjacent Regmentioning
confidence: 99%